PENGARUH MANAJEMEN DANA BANTUAN OPERASONAL SEKOLAH DAN KOMPETENSI GURU TERHADAP HASIL BELAJAR SISWA PADA PRODUK KREATIF KEWIRAUSAHAAN KELAS XII SMKS RADEN RAHMAT MOJOSARI MOJOKERTO - Nuril Zahrotul Jannah; M. Fahim Tharaba; Moh. Padil (STKIP Pesisir Selatan, 2026)
This study aims to analyze the influence of School Operational Assistance Fund (BOS) management and teacher competence on students’ learning outcomes in the Creative Product and Entrepreneurship subject for twelfth-grade students at SMKS Raden Rahmat Mojosari Mojokerto. The study employed a quantitative approach with a causal associative research design. The research population consisted of 766 twelfth-grade students from nine departments, while the sample involved 113 respondents selected using the Slovin technique. Data were collected through Likert-scale questionnaires and analyzed using SPSS version 26. The findings revealed that BOS fund management had a significant effect on students’ learning outcomes, with a significance value of 0.000 and a correlation coefficient of 0.655. Teacher competence also had a significant effect on students’ learning outcomes, with a significance value of 0.000 and a correlation coefficient of 0.790. Simultaneously, BOS fund management and teacher competence contributed 65.1% to students’ learning outcomes. Teacher competence was identified as the most dominant variable influencing learning outcomes compared to BOS fund management. This study highlights that effective educational fund management and professional teacher competence play an important role in improving learning quality and student achievement in vocational schools.